2019
DOI: 10.1002/ptr.6436
|View full text |Cite
|
Sign up to set email alerts
|

β‐Elemene inhibits peritoneal metastasis of gastric cancer cells by modulating FAK/Claudin‐1 signaling

Abstract: Peritoneal metastasis is common in advanced gastric cancer patients and is typically associated with a worse prognosis. β‐Elemene is a natural compound that can be isolated from the Curcuma wenyujin plant and has been widely used in China to treat a variety of cancers. However, the anti‐metastatic impacts of β‐elemene on gastric cancer remain unknown. In our study, we found that β‐elemene significantly inhibited the migration and invasive capacity of gastric cells in vitro and inhibited the capacity of gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Previously, researchers reported that β-elemene prevents the migration of various cancer cells, such as cells of bladder cancer, cells of melanoma, cells of lung cancer, cells of stomach cancer, cells of cervical cancer and cells of breast cancer [ 15 , 23 , 24 , 25 , 26 , 27 ]. In our study, using a wound healing assay, we discovered that β-elemene inhibits the migration of human glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, researchers reported that β-elemene prevents the migration of various cancer cells, such as cells of bladder cancer, cells of melanoma, cells of lung cancer, cells of stomach cancer, cells of cervical cancer and cells of breast cancer [ 15 , 23 , 24 , 25 , 26 , 27 ]. In our study, using a wound healing assay, we discovered that β-elemene inhibits the migration of human glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, β-elemene is present not only in Cannabis sativa but also from Curcuma rhizome, and it is commonly used in traditional Chinese medicine due to its anticancer properties with no reported severe side effects [180]. In this way, this compound has been extensively studied as an anticancer agent in vitro and in vivo and has been demonstrated to be a promising drug for the treatment of a wide variety of tumors [181][182][183][184][185][186]. Among the challenges associated to cancer treatment, it is the development of multidrug resistance (MDR), which negatively impacts the effect of chemotherapy drugs, and consequently treatment success.…”
Section: β-Elemenementioning
confidence: 99%
“…34 Recent studies have reported that β‐elemene significantly inhibited the migration and invasive capacity of BGC823, SGC7901 and multidrug resistant (MDR) SGC7901/ADR gastric cancer cells, TE-1 and KYSE-150 esophageal cancer cells in vitro and inhibited the capacity of BGC823 cells to diffuse peritoneally and metastasize in vivo. 24,25,31 Moreover, the radio sensitivity of cancers, such as glioblastoma multiforme U87-MG, T98G, and U251 cells, 32 melanoma A375 cells, 44 and A549 lung adenocarcinoma xenograft 27,28 were also reported to be significantly enhanced by β-elemene.…”
Section: Pharmacologymentioning
confidence: 99%
“…26,27,29,33,35,37 In addition, β-elemene performed synergistic or directly suppressive effects through targeting histone H1, 23 copper transporter 1 (CTR1), 30 E3 ubiquitin ligase Cbl, 36 signal transducer, and activator of transcription 3 (Stat3), DNA methyltransferase 1 (DNMT1), enhancer of zeste homolog 2 (EZH2), 34 hypoxia inducible factor 1 subunit α (HIF1α), vascular endothelial growth factor A (VEGFA), 39 PTEN, 31 and ataxia telangiectasia mutated (ATM) signaling pathways. 32 Furthermore, β-elemene inhibited tumor angiogenesis and metastasis through regulation of crucial molecules, such as Claudin-1 by downregulating FAK phosphorylation, 24 MMP-2/9 via modulating Cbl-b/EGFR/ERK/AKT signaling 25 and programmed cell death 1-ligand 1 (PD-L1) by regulating p-AKT. 31 β-Elemene was also found to reverse epithelial-mesenchymal transition (EMT) in MDR gastric cancer cells by inhibiting the transcription factors ZEB1 and ZEB2 that contribute to antitumor metastatic activities.…”
Section: Pharmacologymentioning
confidence: 99%